The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s42399-021-00850-2
|View full text |Cite
|
Sign up to set email alerts
|

US Obesity Mortality Trends and Associated Noncommunicable Diseases Contributing Conditions Among White, Black, and Hispanic Individuals by Age from 1999 to 2017

Abstract: This study aims to assess the effect of obesity as an underlying cause of death in association with four main noncommunicable diseases (NCDs) as contributing causes of mortality on the age of death in White, Black, and Hispanic individuals in the USA. To estimate mortality hazard ratios, we ran a Cox regression on the US National Center for Health Statistics mortality integrated datasets from 1999 to 2017, which included almost 48 million cases. The variable in the model was the age of death in years as a prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
(42 reference statements)
0
4
0
1
Order By: Relevance
“…The average age of death was 57.3 years of age for individuals with obesity in all groups and those who died were 15.4 years younger than those who did not have obesity [20]. Although Hispanics in the U.S. have a higher frequency of diabetes and CVD, they also have the smallest mortality hazard ratio for obesity as an underlying cause of death when associated with CVD and cancer [19].…”
Section: Obesity Rates According To Age Sex and Ethnic Groups: Focus ...mentioning
confidence: 94%
See 1 more Smart Citation
“…The average age of death was 57.3 years of age for individuals with obesity in all groups and those who died were 15.4 years younger than those who did not have obesity [20]. Although Hispanics in the U.S. have a higher frequency of diabetes and CVD, they also have the smallest mortality hazard ratio for obesity as an underlying cause of death when associated with CVD and cancer [19].…”
Section: Obesity Rates According To Age Sex and Ethnic Groups: Focus ...mentioning
confidence: 94%
“…Current studies measure the outcome of obesity as a fundamental reason of death as compared to non-communicable diseases (NCDs) in the U.S. as a causative root of mortality among Caucasian, Black, and Hispanic individuals. Diabetes caused a higher mortality rate for individuals with obesity than NCD-related conditions during the years 1999 to 2017 with Caucasians having the highest rate when matched with Black and Hispanic individuals [19]. Hispanics had lower mortality rates for cardiovascular disease (CVD) and diabetes.…”
Section: Obesity Rates According To Age Sex and Ethnic Groups: Focus ...mentioning
confidence: 99%
“…В рамках эпидемиологического исследования ЭССЕ-РФ 2 были отмечены значимые ассоциации ишемической болезни сердца (ИБС) с ожирением, особенно с абдоминальным ожирением, не имеющие гендерных особенностей [2,3]. Люди, имеющие ожирение как основную причину смерти, в среднем на 15,4 года моложе людей без ожирения [4]. Индекс массы тела (ИМТ) считается золотым стандартом для диагностики ожирения, но он не является достоверным показателем телосложения, так как не может показать региональное распределение жировой ткани в организме.…”
Section: кардиологияunclassified
“…2,3 In a study in the United States, it was reported that obesity can shorten the lifespan of patients by about 15.4 years compared to that of normal-weight individuals. 5 Therefore, weight-management programs are recommended to reduce the risk of both morbidity and mortality. The U.S. National Institutes of Health reported that a constant multidimensional weight-control program that includes diet, exercise, and behavioral therapy is effective.…”
Section: Introductionmentioning
confidence: 99%